Analysis of Musculoskeletal Disorders Complaints among Ikat Weaving Craftsmen in Langa Bajawa, Ngada, East Nusa Tenggara in 2022 - Agostin Nofembriyani Djawa; Muntasir; Soleman Landi (Journal of Health Promotion and Behavior, 2023)
Background: Ikat weavers work manually and non-stop for a long duration of time, which increases the risk of occupational diseases such as musculoskeletal disorders (MSDs). Ikat weaving craftsmen perform work manually and non-stop for a long duration of time which generates occupational diseases such as musculoskeletal disorders (MSDs). This study aimed to determine the analysis of complaints of musculoskeletal disorders (MSDs) among ikat weavers in Langa Bajawa Subjects and Method: A cross-sectional study were conducted from August to September 2022 among ikat weaving craftsmen in Langa Bajawa region, Ngada, East Nusa Tenggara. A total of 38 subjects were included in this study. The dependent variable was complaints of musculoskeletal disorders (MSDs). The independent variables were age, working period, duration of work, body posture, work-load, repetitive activity, stretching, and back rest. The data were collected with study questionnaires, Nordic Body Map questionnaires, Rapid Upper Limb Assessment (RULA) questionnaires, and observations. The data were analyzed using Chi-square. Results: Age >35 years (OR= 1.07; 95% CI= 1.07 to 17.79; p= 0.034), working period >10 years (OR= 3.85; 95% CI= 0.98 to 15.12; p= 0.049), posture with RULA score >4 (OR= 5.66; 95% CI= 1.36 to 23.46; p= 0.013),  working hours >8 hours/day (OR= 10.5; 95% CI= 2.16 to 51.42; p= 0.002), repetitive activity (OR= 11.55; 95% CI= 2.41 to 55.39; p= 0.001), rarely stretching (OR= 0.04; 95% CI= 0.00 to 0.27; p< 0.001), and not having a backrest (OR= 0.09; 95% CI= 0.02 to 0.44; p= 0.001) had a significant effect on complaints of musculoskeletal disorder in ikat weaving craftsmen. Meanwhile, the workload of a person who has a pulse of (> 125 BPM) affected the complaints of MSDs, however, it was statistically insignificant. Conclusion: Age >35 years, working period >10 years, posture with a RULA score of >4, working hours >8 hours/ day, repetitive activities, rarely stretching, not having a backrest, and the workload of a person with a pulse rate (> 125 BPM) affect complaints of musculoskeletal disorder in ikat weaving craftsmen. Keywords: complaints of musculoskeletal disorders, craftsmen, ikat weaving. Correspondence: Agostin Nofembriyani Djawa. Faculty of public Health, Universitas Nusa Cendana. Jl. Adi Sucipto Penfui, Penfui, Maulafa, 85001, Kupang, East Nusa Tenggara, Indonesia. Email: agostinnofembriyanidjawa@gmail.com. Mobile: +62 823-1135-6914.